THE EFFECTIVENESS OF USING VIDEO AND ROLE PLAY IN TEACHING SPEAKING - Shanty, Halim (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2016)
This research is aimed at (1) to find out the effectiveness of using role play to develop the studentsâ speaking skill (2) to find out the effectiveness of using video to develop the studentsâ speaking skill (3) to find out which one is more effective between the use of role play and video in teaching speaking.Â  This research used quasy experimental research.Â  It was conducted in ten meetings for each classes at Politeknik Negeri Ujung Pandang Makassar. 12 students for video class and 12 students for role play class. The instruments used in collecting the data was speaking test. In calculating the data, the researcher used SPSS Program version 20. The findings of this research show that (1) using role play is effective in developing the studentsâ speaking skill. It was proven by the significant difference between the studentsâ mean score of pretest and posttest. the mean score of the students in the pretest was 4.1 and the mean score of posttest was 9.5.Â  The t test was 11.19.Â  (2) Using video is effective in developing the studentsâ speaking skill.Â  It was proven by there was a significant difference between the studentsâ mean score of pretest and posttest. the mean score of the students pretest was 4.1 and the mean score of posttest was 9.5.Â  The t test was Â 10.72. (3).Â  Based on statistic analysis, it shows that using role is more effective than video in teaching speaking. The t test result of role play is greater than t test of video class. (11.19 >10.72)